Myosin-V is a mechanical ratchet - Gebhardt, J. Christof M. (National Academy of Sciences, 2006)
Myosin-V is a linear molecular motor that hydrolyzes ATP to move processively toward the plus end of actin filaments. Motion of this motor under low forces has been studied recently in various single-molecule assays. In this paper we show that myosin-V reacts to high forces as a mechanical ratchet. High backward loads can induce rapid and processive backward steps along the actin filament. This motion is completely independent of ATP binding and hydrolysis. In contrast, forward forces cannot induce ATP-independent forward steps. We can explain this pronounced mechanical asymmetry by a model in which the strength of actin binding of a motor head is modulated by the lever arm conformation. Knowledge of the complete force–velocity dependence of molecular motors is important to understand their function in the cellular environment.